System Quality and Information Quality to Use of Simpus: Technology Acceptance Model Perspective - Putrawan, Syach Fitra Wahyu; Nugraha, Jaka (Journal of Office Administration : Education and Practice, 2024)
This research aims to analyze the influence of system quality and information quality on using the community health center management information system at the UPT Tanggunggunung Community Health Center. In the context of primary health services in Indonesia, community health centers have a crucial role, so the effective implementation and use of campus are essential. System quality and information quality are two key factors that are believed to influence the level of use of community health center management information systems. The research method used is quantitative with explanatory research. The subjects of this research were 54 employees of the Tanggungunung Community Health Center with a sampling technique using saturated samples. Data was collected through a questionnaire distributed to the Tanggunggunung Community Health Center employees—data analysis techniques using Structural Equation Modeling-Generalized Structured Component Analysis (SEM-GSCA). The research results show that system quality has a significant favorable influence on node usage. This indicates that the better the quality of the system which includes aspects such as reliability, responsiveness, and ease of use, the higher the level of use of the Simpus by community health center employees. In addition, information quality was found not to have a significant positive influence on node usage. This means that the accurate, relevant, and timely information provided by Simpus still does not increase the user’s tendency to utilize the system.